Analisis Krisis Penegakan Hukum terhadap Penyalahgunaan Merek Arc’teryx dalam Perspektif Undang-Undang Nomor 20 Tahun 2016 - I Dewa Made Satya Dwisadewa; Dewa Ayu Putri Sukadana; I Gede Agus Kurniawan; Ni Putu Sawitri Nandari (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Businesses build trademarks to promote products or services while maintaining their reputation and competitiveness. However, the practice of using well-known brands without the license owner's permission is still found. The case of counterfeiting the Arc'teryx brand by PT ATX Asia Sport Products demonstrates a violation of the exclusive rights of the brand owner. This study aims to analyze law enforcement against the circulation of counterfeit Arc'teryx products in Bali based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications and review the role of the TRIPs Agreement in protecting brands in Indonesia. The method used is normative with a literature review of laws, books, journals, and literature related to unauthorized trademark infringement. The results show that the use of the Arc'teryx brand without official permission confirms the weak supervision and law enforcement of foreign brands that have not been registered in Indonesia. Although the first-to-file system applies, Indonesia still provides legal protection for foreign brands through its membership in the Paris Convention and the TRIPs Agreement. This study emphasizes the need to strengthen the role of the Directorate General of Intellectual Property Rights (DJKI), the Commercial Court, and increase public legal awareness to prevent trademark infringement and create legal certainty for rights owners and consumers.